2008
DOI: 10.2478/s11536-008-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Possible feto-maternal clinical risk of the Kristeller’s expression

Abstract: AbstractThe aim of this clinical case study is evaluation of possible intrapartal complication of the uncritical Kristeller’s expression. In this retrospective clinical study, data on seven parturients with significant maternal or fetal intrapartum complications during the second labor stage and Kristeller expression, associated with the maneuver, were analyzed. Data was obtained from patient files: history of delivery delivery room protocol and neonatal reports from two tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The potential risk factors certainly include traumatic events, as well as aggressively applied fundal pressure and hyperpolysystolie. (6,7) A case is described of complete left-sided intrapartum uterine avulsion with posterior cervical rupture in a secundipara following vacuum extraction. To the best of our knowledge, a similar report has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…The potential risk factors certainly include traumatic events, as well as aggressively applied fundal pressure and hyperpolysystolie. (6,7) A case is described of complete left-sided intrapartum uterine avulsion with posterior cervical rupture in a secundipara following vacuum extraction. To the best of our knowledge, a similar report has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…And regardless of the intention, the fact remains that research has widely found the practice to have the potential for harm, with WHO expressively not recommending it 4 and most national midwifery councils and colleges acknowledging the possible damaging consequences. 2 Moving beyond the physical aftereffects, the traumatising nature of being forced into having fundal pressure is deeply felt. Many women responding to the images with their own stories report their feelings of failure, of not having given birth, of their objections being dismissed.…”
Section: Why Is Fundal Pressure Used As a Childbirth Intervention?mentioning
confidence: 99%
“…Of course, the midwives knew the potential complications of using fundal pressure, from complicated lacerations to uterine rupture and shoulder dystocia. 2 They were also aware of my feelings towards the practice. Never once, in a year and a half of working alongside them, had I wavered from my fierce stance against the practice.…”
mentioning
confidence: 99%
“…Cecilin popis odpovídá postupu kontroverzní intervence známé jako Kristellerova exprese, na jejíž škodlivost upozornila řada vědců (např. Habek et al 2008;Mehri, Awonuga 2005). Prudká bolest, kterou Cecily při takovém zákroku pocítila, však nebyla tím nejhorším.…”
Section: Migrace a Ne/schopnost Komunikace Při Poroduunclassified